Fisheries Carrying Capacity of Joto Reservoir, Lamongan District In The Development of Culture Based Fisheries - Fuquh Shaleh; Endah Sih Prihatini; Ika Purnamasari; Bhiaztika Riztyanadi; Madkuri (Indonesian Society of Limnology, 2024)
Joto Reservoir is the largest reservoir in Tikung District and Lamongan District with a standard area of 113 ha. This reservoir is larger than Tuwiri Reservoir 84 ha and Takeran Reservoir 72 ha. The utilization of Joto Reservoir is currently still not optimal without proper management even though the trophic status of the reservoir waters is hypereutrophic. Therefore, the purpose of this study is to analyze the carrying capacity of Joto Reservoir and to analyze the types of fish and the right amount of seeds to be spread in the development of culture based fisheries. The analysis of fisheries carrying capacity determination uses the results of primary water productivity with the Beveridge Index. The results of this study state that the carrying capacity of natural fisheries in Joto Reservoir is 33.8 tons/year. And the right type of fish in the development of culture based fisheries in Joto Reservoir is freshwater lobster (Cherax quadricarinatus). Freshwater lobster seeds are 2 inches in size with a weight of 2-3 g/piece. The target harvest size of freshwater lobster for consumption is 4-5 inches in size with a weight of around 25-45 g/piece. So the number of freshwater lobster seeds that are spread in the development of aquaculture-based capture fisheries in Joto Reservoir is 916,902 tails/year or 305,634 tails/4 months.